God Image: A Comparative Study of Psychology and Sufism - Said Aqil S, Rihab (Jurnal Locus Penelitian dan Pengabdian, 2026)
The concept of the image of God has gained increasing attention in contemporary scholarship due to its significant role in shaping psychological well-being and spiritual life. Psychological studies conceptualize the image of God as a subjective, relational construct shaped by attachment patterns, emotional experiences, and sociocultural contexts. In contrast, theological and Sufi perspectives emphasize cognitive-spiritual capacity and inner purification in understanding divine reality. However, existing research remains largely dominated by Western frameworks, with limited integration of Islamic and Sufi insights, particularly in Muslim contexts. This study aims to examine the formation of the image of God through a comparative analysis of psychology and Sufism and to develop an integrative framework within Islamic psychology. It employs a qualitative library research design using a comparative-integrative method. Data were drawn from primary and secondary sources indexed in Google Scholar and Scopus, including classical Sufi texts and contemporary psychological literature. Analysis was conducted through qualitative content analysis, thematic categorization, and systematic comparison, supported by a hermeneutic approach. The findings indicate that both perspectives view the image of God as a dynamic construct shaped by subjective experience and capable of transformation across the lifespan. However, they differ in epistemological orientations, determinants, and goals of transformation. Psychology emphasizes empirical and adaptive reconstruction, whereas Sufism highlights normative-spiritual refinement leading to ma‘rifah. Integrating these perspectives offers a more comprehensive framework for addressing psycho-spiritual issues within Islamic psychology.